Strategies for Transition to Clean Energy: Household Cooking in Panama (LACCEI, 2024)
This paper presents the planning and implementation of a program to replace traditional energy sources such as Liquefied Petroleum Gas and firewood for electricity, based on the analysis of different data from the domestic sector in Panama. The main steps and indicators that must be taken into account when making a proposal to plan and implement a polluting fuel substitution program are shown, proposing in the first place to carry out a market study to detect market failures that may affect implementation: barriers cultural, financial, institutional, lack of objective data. 3 different approaches are proposed, including strategies and tactics that could be clearly stated and transparently executed. The results generated from this evaluation will help guide investment objectives, prioritize needs and customize the evaluations to the needs of end users to achieve the transition from traditional fuels to electricity in the domestic sector.